Echoes without resonance critiquing certain aspects of recent scholarly trends in the study of the Jewish Scriptures in the New Testament - Foster, Paul 1966-; Beale, G. K. 1949- (2015)
The study of the use of the Old Testament in the New Testament (OT/NT)